Regulation Reconstruction on Female Genital Cosmetic Surgery for Sexual Violence Victims in Indonesia Under Dignified Justice - Ananingati, Ananingati; Mashdurohatun, Anis; K W, Jaka; K W, Jaka (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to reconstruct regulations concerning female genital cosmetic surgery for victims of sexual violence in Indonesia by employing a dignified justice approach that integrates the values of positive law and Islamic law. The increase in cases of sexual violence has significantly impacted victims, both physically, psychologically, and spiritually. Although Law No. 12 of 2022 on Sexual Violence Crimes has provided a legal framework for victim protection, regulations related to female genital cosmetic surgery remain inadequate and are not comprehensively regulated. This research recommends the formulation of holistic regulations based on dignified justice. Furthermore, support based on Islamic values, such as takaful and rahmatan lil-alamin, should be integrated into victim rehabilitation services to provide comprehensive protection. Public education is also a priority to reduce social stigma against victims of sexual violence, which often hinders their recovery process. By applying the principles of dignified justice and the values of Islamic law, the resulting regulations are expected to provide comprehensive protection, support the physical and psychological recovery of victims, and uphold their dignity as creations of Allah. This research is anticipated to make a significant contribution to the development of public policies that are more responsive to the needs of victims of sexual violence in Indonesia and to raise public awareness about the importance of protection for them.